2022
DOI: 10.2217/fon-2022-0071
|View full text |Cite
|
Sign up to set email alerts
|

Cancer staff in an NHS cancer center: infections, vaccination, stress and well-being support during the COVID-19 pandemic

Abstract: Aim: To evaluate the impact of the pandemic on the well-being of cancer staff and determine the uptake of opt-in mitigation strategies. Materials & methods: Staff at Guy's Cancer Centre (London, UK) participated in an anonymized survey between May and August 2021. Results: Of 1182 staff, 257 (21.7%) participated. Ethnicity (p = 0.020) and comorbidity burden (p = 0.022) were associated with SARS-CoV-2 infection status. Of 199 respondents, seven (3.6%) were vaccine-hesitant, which was associated with low flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Many studies have shown that the administration of COVID‐19 vaccine to patients receiving ICIs may result in an increased risk of irAEs due to the immunogenic effect of vaccination 66,67 . To date, there is insufficient evidence to confirm the correlation between both COVID‐19 vaccine and ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the administration of COVID‐19 vaccine to patients receiving ICIs may result in an increased risk of irAEs due to the immunogenic effect of vaccination 66,67 . To date, there is insufficient evidence to confirm the correlation between both COVID‐19 vaccine and ICIs.…”
Section: Discussionmentioning
confidence: 99%